Are urinary PAHs biomarkers of controlled exposure to diesel exhaust?. (June 2014) - Lu, Sixin S.; Sobus, Jon R.; Sallsten, Gerd; Albin, Maria; Pleil, Joachim D.; Gudmundsson, Anders; Madden, Michael C.; Strandberg, Bo; Wierzbicka, Aneta; Rappaport, Stephen M.
Abstract Urinary polycyclic aromatic hydrocarbons (PAHs) were evaluated as possible biomarkers of exposure to diesel exhaust (DE) in two controlled-chamber studies. We report levels of 14 PAHs from 28 subjects in urine that were collected before, immediately after and the morning after exposure. Using linear mixed-effects models, we tested for effects of DE exposure and several covariates (time, age, gender and urinary creatinine) on urinary PAH levels. DE exposures did not significantly alter urinary PAH levels. We conclude that urinary PAHs are not promising biomarkers of short-term exposures to DE in the range of 106–276 µg/m3.